Nutritional Fulfillment of the first 1000 Days Based on Local Food Ingredients as A Strategy for Handling the Stunting Problem - Retnaningsih, Yuliantisari; Waryana; Wijanarka, Agus (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2023)
This community service activity aims to increase the knowledge of mothers in meeting the nutritional needs of 1000 HPK based on local food. Community service activities were carried out on Saturday, 19 August 2023 at Posyandu Melati, Panggungharjo Village, Sewon, Bantul. The target was cadres and mothers totaling 60 participants. The method used is lecture, question, and answer. Community service activities are related to providing knowledge and understanding about local food-based products as an effort to overcome the problem of stunting. Evaluate community service activities by assessing the pretest and posttest regarding stunting knowledge. The posttest was carried out after participants received information about stunting. The average results of the pretest and posttest were 60.5 and 90.5, respectively, measured at the knowledge level.. The conclusion there was an increase in the level of knowledge of mothers about stunting after being given lectures and questions and answers.